Mixed culture polyhydroxyalkanaotes (PHA) production using crude glycerol as carbon source / Ainil Hawa Mohamad Fauzi - Ainil Hawa , Mohamad Fauzi (2020)
Polyhydroxyalkanoates (PHA) is a biopolymer that has the prospect of becoming a preferred renewable and environmentally friendly resource with various applications including in manufacturing and medicine. Intensive studies have been carried out to find the most practical and economical method for PHA production because current commercial production of PHA is stringent and extremely costly. The aim of this study is to enrich PHA-accumulators with high PHA production capabilities by evaluating the stability of the enrichment process and by observing the effect of organic loading rate (OLR) on the production potential. In this study, PHA-accumulators were cultivated using activated sludge with crude glycerol in a sequencing batch reactor (SBR). An aerobic dynamic feeding (ADF) strategy was employed for the enrichment process. This is then followed by production tests in a batch reactor to test for the maximum PHA production. This study successfully maintained a long-term enrichment operation where the PHA-accumulators produced a maximum PHA content of 80 wt % in biomass dry weight. A production yield of 0.7 mg C PHA/mg C substrate was obtained with a productivity ranging from 193 mg/(L∙h) to 236 mg/(L∙h) where the maximum production time is 6 hours. The increase of OLR was found to have insignificant effect on the final PHA production. However, it highlighted the robustness of the enriched PHA-accumulators and had significant effect on the biomass concentration. The increase of OLR from 360 mg C/(L∙d) to 1000 mg C/(L∙d) led to the increment of biomass concentration from less than 0.7 g/L to 2 g/L. An OLR of 1000 mg C/(L∙d) was the iv highest OLR feasible in this study and a higher OLR of 1250 mg C/(L∙d) was found to be detrimental to the enrichment stage. The PHA-accumulators were found to accumulate a copolymer with 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (3HV) monomers at a HB:HV of 60:40. The PHA-accumulators were observed to be highly robust and the accumulation of copolymers is eminently a promising attribute. The feasibility of directly using waste substrate and mixed cultures for PHA production can help reduce the PHA production operational costs. This method also provides an option for resource recovery operation in converting waste to value-added products, paving the way for a more sustainable process.